ANALISIS YURIDIS SUBROGASI DENGAN PENGALIHAN KREDIT YANG TERIKAT HAK TANGGUNGAN PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. CABANG KABANJAHE - LUCY MARGARETH NAPITUPULU (Ilmu Hukum Prima (IHP), 2021)
All business sectors or individuals today and in the future cannot be separated from banking sector. In order to balance and harmonize this need, the role of bank is to provide loan fund through loan. Kabanjahe Branch Office of BRI, in providing loans, makes efforts and competes to create innovations to their products as their strategies to get prime consumer debtor candidate including debtors who performs loan takeover. Loan takeover that is bound with mortgage right in Kabanjahe Branch Office of BRI is the provision of new loans to consumer debtor, which aims to pay consumer debtor’s ongoing loans, with land title as mortgage rights of the loan that is bound with mortgage right in the older bank, so that Kabanjahe Branch Office of BRI replaces rights of the older bank. Loan takeover that is bound with mortgage rights in Kabanjahe Branch Office of BRI is related to the provisions of subrogation in the Civil Code.This research employs empirical juridical method which is descriptive. It describes, studies, explains, and analyzes theoretical and practical legal regulations on mechanism and legal consequences for loan takeover that is bound with mortgage right in Kabanjahe Branch Office of BRI, and whether the loan takeover is in line with the provisions of subrogation in the Civil Code.The results of the research explains the mechanism of loan takeover. It is done by submitting an application for loan by candidate consumer debtor to be processed, and then the loan is realized and transferred. The legal consequences for loan takeover is the emergence of a loan agreement between customer debtor and Kabanjahe Branch Office of BRI and the termination of the loan agreement between the customer debtor and the older bank; the elimination of mortgage right for and in the name of the older bank and the emergence of mortgage right for and in the name of Kabanjahe Branch Office of BRI; the termination of the position of older bank as creditor and holder of the mortgage right of customer debtor and mortgage right grantor. The implementation of the loan takeover that is bound with mortgage right in Kabanjahe Branch Office of BRI has been in line with the provision son subrogation, namely Article 1400 of the Civil Code, particularly Article 1400 sub 2 of the Civil Code.It is suggested that the Law further regulate provisions on subrogation that are in line with the banking development today, so that loan takeover that is bound with mortgage right can fully/completely implement the provision on subrogation as well in the future. It is expected that more references discuss about the legal consequences for loan takeover that is bound with mortgage right. It is also expected that subrogation be introduced and implemented again in banking practice and Notary, because it is in line with the provision son subrogation in the Civil Code.